The prevalence and correlates of obstructive lung disease among adults aged 45 and above in India: Findings from the longitudinal aging study in India - T. V. Sekher; Emma Nichols; Sundeep Salvi; Sarang P. Pedgaonkar; Crystal M. North; Sarah Petrosyan; David E. Bloom; Jinkook Lee (PLoS ONE, 2025)
Despite its high disease burden, few existing estimates of the prevalence of obstructive lung disease in India are based on high-quality data sources. To our knowledge, prior studies at the national level have not included objective measurements of lung function. The Longitudinal Aging Study in India administered spirometry to adults 45 years and older (N = 31,103). We estimated inverse probability weights to account for sample selection processes and quantified the prevalence of obstructive lung disease overall and by region, age, and gender. We investigated the overlap among objective rates of obstructive lung disease, respiratory symptoms, and self-reported diagnoses. Additionally, we evaluated associations between obstructive lung disease and pertinent risk factors. The overall prevalence of obstructive lung disease was 14.4% (95% confidence interval [CI] 13.4–15.4). Prevalence was higher among men than women (p < 0.001) and increased with age (p < 0.001). Disease awareness was low, with only 12.0% (95% CI 9.9–14.5) of men and 11.0% (95% CI 8.6–14.0) of women with obstructive lung disease reporting prior diagnoses of lung disease. We observed heterogeneity by region (p < 0.001), which largely remained after accounting for differences in demographic and risk factors. High prevalence and low disease awareness highlight important challenges in the prevention and management of obstructive lung disease in India. Multifaceted approaches are needed to address this disease burden, including understanding and lowering exposure to risk factors and improving infrastructure and resources for diagnosing and managing obstructive lung disease.